Réhabiliter l’Homme avec la technologie - Stéphane Simonian (Recherches en Éducation)
The tension between a functionalist and phenomenological approach artifacts suggests two conceptions of technology. The first one, functionalist approach or "utilitarian", aims at knowing what an artifact can do; the second to an artifact can understand. This double issue will be developed in a philosophical approach, relying in particular on the thought of Simondon (1958). In this perspective the debate deals with the look worn by men over men in the introduction or use of technology. Is it possible to reduce man to a "technical person"? The technology enable to enhance the "phenomenological" dimension of men? These central questions are a special place in the educational and formative sector which attempts to introduce technology are always delicate animating often heated debates between supporters and technophobic. It this article, we puprose a "unifying" approach to the relationship between man and technology considering technology as a way to ennoble the human in that it has more specific (to interpret, understand, remedy of error, etc.), to release certain functional requirements to enable it being to the world and in the world. One consequence is to change point of view about technology, for example, recognizing that train teachers, students, technology is also to form them without technology.